1977
DOI: 10.1111/j.1432-1033.1977.tb11912.x
|View full text |Cite
|
Sign up to set email alerts
|

The Replication of Ribosomal DNA in Physarum polycephalum

Abstract: The DNA coding for ribosomal RNA in Physarum polycephalum exists as a collection of extrachromosomal molecules of molecular weight 37 x lo6. We have investigated the replication of rDNA, with the following results. (a) Replication of rDNA is unscheduled. This means that molecules that are replicated at any particular time in one mitotic cycle have an equal probability of replicating again in each time interval in the subsequent cycle. Similarly, in a single cycle, some molecules replicate more than once, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
44
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 22 publications
5
44
0
Order By: Relevance
“…During vegetative growth the extrachromosomal rDNA copies replicate autonomously. In Physarum polycephalum replication of rDNA palindromes occurs throughout the S and G2 cell cycle stages, and some, but not necessarily all, rDNA palindromes serve as replication templates (33). Similar changes to those observed in this work in the relative proportions of polymorphic rDNA palindromes and effects on rDNA inheritance were observed during the sexual cycle of Physarum polycephalum (6).…”
Section: Resultssupporting
confidence: 73%
“…During vegetative growth the extrachromosomal rDNA copies replicate autonomously. In Physarum polycephalum replication of rDNA palindromes occurs throughout the S and G2 cell cycle stages, and some, but not necessarily all, rDNA palindromes serve as replication templates (33). Similar changes to those observed in this work in the relative proportions of polymorphic rDNA palindromes and effects on rDNA inheritance were observed during the sexual cycle of Physarum polycephalum (6).…”
Section: Resultssupporting
confidence: 73%
“…to isolate extrachromosomal doublestranded rDNA molecules of 38 x 106 daltons from chromosomal DNA (3,24 extrachromosomal molecules, and further examination by electron microscopy revealed that 95% or more of the molecules were linear (data not given).…”
Section: Resultsmentioning
confidence: 99%
“…The cover slip was removed, and the slide was rinsed in running cold water, placed in 7.5% K3Fe(CN)6 for 20 min at 22°C, rinsed several times with water, placed in 12% Na2S203 for 5 Extraction and sizing of extrachromosomal DNA. Nuclei from 12 2-mm root tips were extracted by the method of Hirt (10), which separates extrachromosomal DNA in the supernatant from chromosomal DNA that precipitates as a pellet (3,24 pl (-20 ,ug) of marker DNA, and 1.65 ml of SSC. The mixture was centrifuged for 16 h at 36,000 rpm at 25°C in a Beckman Ti 65 rotor.…”
Section: Methodsmentioning
confidence: 99%
“…The clearest evidence for specific origins has been obtained in studies of certain extrachromosomal DNAs: the extrachromosomal rDNA in Physarum polycephalum and Tetrahymena thermophilia (6,42,43) and the 2,1 plasmid of yeasts (30). Evidence that chromosomal origins may occur nonrandomly comes from studies with certain repeated DNAs: the rDNAs of several species (2,3,28) and the amplified dihydrofolate reductase genes of a Chinese hamster cell line (18,19); however, the resolution of these studies has not been sufficient to determine whether initiation occurs at a specific nucleotide sequence or anywhere within a relatively long stretch of DNA.…”
mentioning
confidence: 99%
“…3 (3,18) or analysis of replicating molecules identifiable by electron microscopy such as plasmids (30), extrachromosomal DNA (6,42,43), and purified ribosomal DNA repeats (2,3,28). If enough replicating DNA can be obtained, the method described in this paper will allow location of origins in stretches of unique chromosomal DNA.…”
mentioning
confidence: 99%